2020
DOI: 10.3390/s20185132
|View full text |Cite
|
Sign up to set email alerts
|

Classification and Prediction of Typhoon Levels by Satellite Cloud Pictures through GC–LSTM Deep Learning Model

Abstract: Typhoons are some of the most serious natural disasters, and the key to disaster prevention and mitigation is typhoon level classification. How to better use data of satellite cloud pictures to achieve accurate classification of typhoon levels has become one of classification the hot issues in current studies. A new framework of deep learning neural network, Graph Convolutional–Long Short-Term Memory Network (GC–LSTM), is proposed, which is based on the data of satellite cloud pictures of the Himawari-8 satell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Overall, the 5 × 5 convolution kernel extracted satellite cloud image information more effectively than the other kernels. This result is consistent with that of Zhou et al [12], who found that the 5 × 5 convolution kernel had an obvious feature extraction effect for satellite cloud image characteristics. 2.…”
Section: Different Performances With Various Convolution Kernel Sizessupporting
confidence: 93%
See 2 more Smart Citations
“…Overall, the 5 × 5 convolution kernel extracted satellite cloud image information more effectively than the other kernels. This result is consistent with that of Zhou et al [12], who found that the 5 × 5 convolution kernel had an obvious feature extraction effect for satellite cloud image characteristics. 2.…”
Section: Different Performances With Various Convolution Kernel Sizessupporting
confidence: 93%
“…Some progress has also been made in identifying satellite cloud images using different cloud cluster features [10,11]. Zhou et al [12] accurately identified the eye and cloud wall of typhoons and used the GC-LSTM model to accurately recognize and predict typhoon intensity. Zhao et al [13] proposed a real-time typhoon eye detection method based on deep learning with satellite cloud images, which provided important data for detecting real typhoon information.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the number of iterations t , SAE-GLSTM computes the hidden forward sequence as and the hidden backward sequence as , and the output sequence is represented as Y . The input x t has a hierarchical timing layer and the transition of the node state is declared a vector using the standard LSTM ( Zhou, Xiang & Huang, 2020 ). Figure 5 shows the hierarchical forward and backward timing structure of Graph LSTM.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…Precipitation nowcasting can forecast the distribution and development of precipitation in nearby periods with high temporal and spatial resolution. Accurate precipitation nowcasting can not only provide convenience for people's daily life [1,2] but also help in disaster prevention and mitigation [3,4]. The current common operational system for precipitation forecasts is the numerical weather prediction (NWP) [5] model, but it cannot provide accurate nowcasting due to spin-up [6].…”
Section: Introductionmentioning
confidence: 99%